Mental Competence, Caregivers, and the Process of Consent: Research Involving Alzheimer's Patients or Others with Decreasing Mental Capacity - Guinn, David E. (Cambridge quarterly of healthcare ethics, 2002)
Alzheimer's disease and other forms of dementia are among the fastest growing health problems in America. Dementia incidence tends to increase with age, and the elderly are the fastest growing segment of the population. Medical and social sciences research on dementia involving demented patients is both ongoing and necessary. However, as noted in a report of the Office for Human Subjects Research, “while research with intellectually impaired people generates valuable … data, it also provides significant ethical challenges.